Dietary mercury intake and colorectal cancer risk: A case-control study. Issue 7 (July 2020) - Kim, Hyejin; Lee, Jeonghee; Woo, Hae Dong; Kim, Dong Woo; Oh, Jae Hwan; Chang, Hee Jin; Sohn, Dae Kyung; Shin, Aesun; Kim, Jeongseon
Summary: Background & aims: The main source of mercury exposure is food such as fish and shellfish. Mercury is a growing concern due to its associations with a number of harmful health effects, including cancer. The objectives of this study were to examine the association between dietary mercury intake and colorectal cancer (CRC) risk and to determine whether this association differs by anatomical site and menopausal status. Methods: A case-control study was conducted with 2769 participants (923 cases and 1846 controls) in Korea. Dietary mercury intake and fish and shellfish consumption were assessed using a semiquantitative food frequency questionnaire. Results: A high intake of dietary mercury was associated with an increased risk of CRC (in the group with lower fish and shellfish consumption; odds ratio (OR): 3.13; 95% confidence interval (95% CI): 2.33, 4.71, in the group with higher fish and shellfish intake; OR: 3.84, 95% CI: 2.20, 7.30) after adjusting for all potential confounders by anatomic site in men. Among women, the results differed by fish and shellfish consumption and menopausal status. Regarding the amount of fish and shellfish intake, a positive association was found only in the group with lower intake (CRC; OR: 2.24, 95% CI: 1.36, 3.72, colon cancer; OR: 2.25, 95% CI: 1.22, 4.16, rectal cancer; OR: 2.28, 95% CI: 1.13, 4.57). In the stratified analysis by menopausal status, the elevated risk of CRC was still observed among both pre- and postmenopausal women depending on anatomical site, except for the colon cancer patients with premenopausal status. Conclusions: A high intake of mercury was associated with an elevated risk of overall CRC. Future large-scale prospective cohort studies are recommended to investigate the causal effects of dietary mercury intake by fish and shellfish consumption on CRC risk depending on anatomical site and menopausal status.